YY SOCIALIZATION AND APPLICATION OF RHIZOBACTERIA IN GINGER CULTIVATION IN THE JORONG BELUBUS INNOVATION FARMING GROUP, NAGARI SUNGAI TALANG, GUGUAK DISTRICT, LIMAPULUH KOTA REGENCY - Yulmira Yanti (Department of Agricultural Product Technology, Faculty of Agricultural Technology, Universitas Andalas Kampus Limau Manis - Padang, Sumatera Barat Indonesia-25163, 2021)
Nagari Sungai Talang is one of the villages in Payakumbuh District, Lima Puluh Kota Regency which seeks to cultivate ginger plants. The type of ginger commonly developed by this Innovation farmer group is elephant ginger. This ginger has a rhizome that is larger and fatter, the rhizome segment is more bulging than other varieties of ginger. This type of ginger can be consumed both when you are young and old, both as fresh ginger and processed ginger. One of the obstacles that hinder our farmers from developing organic ginger here is the low production because the supply of nutrients is also low and the attack of pests and diseases is quite high. Therefore, it is necessary to find a treatment that can overcome this problem to increase the production of organic ginger. One of the microorganisms that is widely reported to act as biological agents is from the Plant Growth Promoting Rhizobacteria (PGPR) group or plant growth promoting rhizobacteria. Rhizobacteria have the ability to aggressively colonize the rhizosphere and some types of rhizobacteria are capable of dual roles as biofertilizers and bioprotectants in plants. The purpose of this farmer group empowerment activity is to provide knowledge about the benefits of Rhizobacterial biological agents in triggering the growth and yield of ginger plants in the field as well as plant-disturbing organisms that often attack ginger plants during cultivation, as well as effective control methods through outreach activities and direct counseling in the field. The method used is the method of socialization, counseling and direct discussion with farmer groups. The results obtained from this empowerment activity are that the farmer groups understand the benefits of Rhizobacteria biological agents as a trigger for growth and production of ginger plants, know various plant pest organisms (OPT) and know how to properly control them.